2007
DOI: 10.1111/j.1572-0241.2007.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication: A Randomized Prospective Study of Triple Therapy Versus Triple Therapy Plus Lactoferrin and Probiotics

Abstract: The results of our study suggest that the addition of bLf and Pbs could improve the standard eradication therapy for H. pylori infection--bLf serving to increase the eradication rate and Pbs to reduce the side effects of antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 37 publications
3
79
0
1
Order By: Relevance
“…The occurrence of side-effects can reduce the compliance with treatment regimens and lead to the development of bacterial resistance. 9 In the EAC 7 group 10 patients (16.7%) were lost to follow-up whereas in the EAC 14 group 12 (20%) were lost to follow-up, but …”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of side-effects can reduce the compliance with treatment regimens and lead to the development of bacterial resistance. 9 In the EAC 7 group 10 patients (16.7%) were lost to follow-up whereas in the EAC 14 group 12 (20%) were lost to follow-up, but …”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was reported that Lactoferrin, the precursor of Lfcin B, has a dramatic inhibitory effect on certain pathogens while probiotics such as Bifidobacterium and Lactobacillus were not affected by Lactoferrin (60). Furthermore, the combination of Lactoferrin with probiotics has been confirmed to have enhanced antibacterial effect in the clinical trials designed to overcome the infections caused by Helicobacter pylori (61). However, the reason that LfcinB inhibited pathogens but not probiotics in animal model experiments and clinical trials remains unclear (62,63).…”
Section: Fig 5 the Kinase Assaysmentioning
confidence: 95%
“…Two recent metaanalyses suggest a modest effect 70,71 . Studies are needed to identify which strains to use and what is the best delivery system to achieve reliable results.…”
Section: Thinking Outside the Box: The Use Of Treatment Enhancersmentioning
confidence: 99%